WILDFIRES IN BRAZIL AND ITS HEALTH IMPACTS: A SYSTEMATIC REVIEW (CIPEEX, 2022)
AIR QUALITY REPRESENTS A GLOBAL HEALTH ISSUE. ONE OF THE BIGGEST CULPRITS FOR AIR IS THE BURNING OF BIOMASS. IN TROPICAL COUNTRIES, SUCH AS BRAZIL, FIRES TEND TO OCCUR INDISCRIMINATELY AND, IN MOST CASES, DUE TO HUMAN ORIGINS. THE OBJECTIVE OF THIS WORK WAS ANALYZED AS EVIDENCE ABOUT THE HEALTH RISKS ARISING FROM FIRES IN REGIONS OF BRAZIL AND IDENTIFIED IN DIFFERENT VARIETIES. THE METHODOLOGY USED WAS A SYSTEMATIC REVIEW OF THE LITERATURE FOLLOWING THE RECOMMENDATIONS OF THE PRISMA GUIDE (PREFERRED REPORTING ITEMS FOR SYSTEMATIC REVIEWS AND META-ANALYSES). THE WORDS IN THE LITERATURE WERE MADE IN THREE ELECTRONIC DATABASES (WEB OF SCIENCE, PUBMED AND VHL), USING "FOREST SEARCH FIRES", "BRAZIL" AND "HEALTH RISKS" AND THEIR RESPECTIVE WORDS IN SPANISH AND ENGLISH AS KEYWORDS. BASED ON THE DESCRIPTORS IN SCIENCES (DECS) AND THE MEDICAL SUBJECT HEADERS (MESH) AND CONSIDERING THE STUDIES PUBLISHED DURING THE PERIOD FROM JANUARY 1, 2011 TO OCTOBER 16, 2021, ON THE RELATIONSHIP BETWEEN EXPOSURE TO FOREST FIRES AND PROBLEMS OF HEALTH NOT BRAZIL. A TOTAL OF 687 ARTICLES WERE IDENTIFIED, OF WHICH 25 MET THE INCLUSION CRITERIA FOR THIS RESEARCH AND WERE THEREFORE INCLUDED FOR ANALYSIS. MOST OF THE STUDIES (80%) WERE CARRIED OUT IN THE AMAZON REGION. EXPOSURE AND CARDIOVASCULAR FIRE AS WELL WERE ASSOCIATED WITH WILDFIRES IN 2% OF STUDIES. AS STUDIES OF STUDIES SEEK TO POINT TO THE RESEARCH STUDIES OF FOREST FIRES TO HEALTH REGIONS OF EXPOSED POPULATIONS AND TO THE NEED FOR MORE ON THIS TOPIC OTHER RESEARCH AND BIOMES IN BRAZIL.
Keywords: Systematic review; Air pollution; Health risks; Mental health